Cannabinoid CB(1) and CB(2) receptor mechanisms underlie cannabis reward and aversion in rats - Spiller, Krista J. (Br J Pharmacol, 2019)
BACKGROUND AND PURPOSE: Endocannabinoids are critically involved in brain reward functions, mediated by activation of CB(1) receptors, reflecting their high density in the brain. However, the recent discovery of CB(2) receptors in the brain, particularly in the midbrain dopamine neurons, has challenged this view and inspired us to re‐examine the roles of both CB(1) and CB(2) receptors in the effects of cannabis. EXPERIMENTAL APPROACH: In the present study, we used the electrical intracranial self‐stimulation paradigm to evaluate the effects of various cannabinoid drugs on brain reward in laboratory rats and the roles of CB(1) and CB(2) receptors activation in brain reward function(s). KEY RESULTS: Two mixed CB(1) / CB(2) receptor agonists, Δ(9)‐tetrahydrocannabinol (Δ(9)‐THC) and WIN55,212‐2, produced biphasic effects—mild enhancement of brain‐stimulation reward (BSR) at low doses but inhibition at higher doses. Pretreatment with a CB(1) receptor antagonist (AM251) attenuated the low dose‐enhanced BSR, while a CB(2) receptor antagonist (AM630) attenuated high dose‐inhibited BSR. To confirm these opposing effects, rats were treated with selective CB(1) and CB(2) receptor agonists. These compounds produced significant BSR enhancement and inhibition, respectively. CONCLUSIONS AND IMPLICATIONS: CB(1) receptor activation produced reinforcing effects, whereas CB(2) receptor activation was aversive. The subjective effects of cannabis depend on the balance of these opposing effects. These findings not only explain previous conflicting results in animal models of addiction but also explain why cannabis can be either rewarding or aversive in humans, as expression of CB(1) and CB(2) receptors may differ in the brains of different subjects.